An automated high-throughput system for phenotypic screening of chemical libraries on C. elegans and parasitic nematodes. Issue 1 (April 2018) - Partridge, Frederick A.; Brown, Anwen E.; Buckingham, Steven D.; Willis, Nicky J.; Wynne, Graham M.; Forman, Ruth; Else, Kathryn J.; Morrison, Alison A.; Matthews, Jacqueline B.; Russell, Angela J.; Lomas, David A.; Sattelle, David B.
Abstract: Parasitic nematodes infect hundreds of millions of people and farmed livestock. Further, plant parasitic nematodes result in major crop damage. The pipeline of therapeutic compounds is limited and parasite resistance to the existing anthelmintic compounds is a global threat. We have developed an INVertebrate Automated Phenotyping Platform (INVAPP) for high-throughput, plate-based chemical screening, and an algorithm (Paragon) which allows screening for compounds that have an effect on motility and development of parasitic worms. We have validated its utility by determining the efficacy of a panel of known anthelmintics against model and parasitic nematodes: Caenorhabditis elegans, Haemonchus contortus, Teladorsagia circumcincta, and Trichuris muris . We then applied the system to screen the Pathogen Box chemical library in a blinded fashion and identified compounds already known to have anthelmintic or anti-parasitic activity, including tolfenpyrad, auranofin, and mebendazole; and 14 compounds previously undescribed as anthelmintics, including benzoxaborole and isoxazole chemotypes. This system offers an effective, high-throughput system for the discovery of novel anthelmintics. Graphical abstract: Image 1 Highlights: A rapid system for quantifying motility and growth of nematodes is described. The system was validated by quantifying the activity of known anthelmintics. The Pathogen Box was screened for molecules blocking C. elegans growth. Compounds with known anthelmintic/anti-parasitic activity were identified. Fourteen compounds previously undescribed as anthelmintics were discovered.